Technical and Economic Analysis of A Biomass Pyrolysis Plant - Chawannat Jaroenkhasemmeesuk (2018)
© 2015 The Authors. Published by Elsevier Ltd. Bio-oil from fast pyrolysis of biomass has great potential to be one of the main renewable energy sources. At present, there are only a small number of commercial bio-oil plants because their operation is rather complicated and the return is not attractive. With funding from the government sector, a small biomass pyrolysis plant (capacity of 20-30 dm 3 of bio-oil per day) was built and operated in Phrae, Thailand. In this paper, practical stepwise methodologies were presented to technically analyze the production and energy consumption of bio-oil production based on the data from this demonstrated plant. Mass and energy balance calculations were carried out to assess the performance and improve process design. An economic analysis was also performed to study the potential of biomass-to-bio-oil conversion costs and viability of commercialization. From the investigation, it was found that the operation cost of crude bio-oil production was about 30-35 Thai baht per dm 3 . Even though the operating cost of the fast pyrolysis units is excessively high under current situation, the biomass plant still has potential to generate attractive economic return if the upgrading process is employed as well as assistance from the government is available to subsidize the sale price.